2019
DOI: 10.1097/brs.0000000000003351
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Patients With Dual Hip and Spinal Degenerative Disease

Abstract: Study Design. Retrospective study. Objective. To determine how lumbar spinal fusion-total hip arthroplasty (LSF-THA) operative sequence would affect THA outcomes. Summary of Background Data. Outcomes following THA in patients with a history of lumbar spinal degenerative disease and fusion are incompletely understood. Methods. The PearlDiver Research Program (www.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The group evaluated 23,584 patients (13,102 THA after LSF; 10,482 THA before LSF) and found that patients who received the THA after LSF demonstrated a greater rate of prosthetic dislocations at 90 days (2.8% versus 0.2%) and 2 years (4.6% versus 1.7). 40 By contrast, Yang et al 41 retrospectively reviewed a national database (PearlDiver Patient Records Database) and compared perioperative outcomes in a group of 3,372 patients (2,016 THA after LSF; 1,356 THA before LSF) and uncovered a greater odds of sustaining a post-THA dislocation in patients who received the THA before the LSF (odds ratio = 2.46 [1.90 to 3.12] versus 1.29 [0.99 to 1.65]). The aforementioned set of conflicting studies demonstrate the lack of clear understanding surrounding the topic of surgical timing and post-THA dislocations in patients who require surgical intervention to address simultaneous hip and lumbar spine pathology; thus, additional analysis is warranted.…”
Section: Discussionmentioning
confidence: 95%
“…The group evaluated 23,584 patients (13,102 THA after LSF; 10,482 THA before LSF) and found that patients who received the THA after LSF demonstrated a greater rate of prosthetic dislocations at 90 days (2.8% versus 0.2%) and 2 years (4.6% versus 1.7). 40 By contrast, Yang et al 41 retrospectively reviewed a national database (PearlDiver Patient Records Database) and compared perioperative outcomes in a group of 3,372 patients (2,016 THA after LSF; 1,356 THA before LSF) and uncovered a greater odds of sustaining a post-THA dislocation in patients who received the THA before the LSF (odds ratio = 2.46 [1.90 to 3.12] versus 1.29 [0.99 to 1.65]). The aforementioned set of conflicting studies demonstrate the lack of clear understanding surrounding the topic of surgical timing and post-THA dislocations in patients who require surgical intervention to address simultaneous hip and lumbar spine pathology; thus, additional analysis is warranted.…”
Section: Discussionmentioning
confidence: 95%
“…These patients also have decreased satisfaction, less improvement with respect to overall pain, and worse quality-of-life measures than those without previous LSF 43,44 . While multiple authors have demonstrated that LSF is a significant risk factor for postoperative dislocation, recent literature has shown that patients with a history of LSF >2 years before the THA had no increase in dislocations or 30-day complications, but there was a significant increase in the THA revision rate 5,6,[45][46][47] . Therefore, a discussion with the patient regarding expectations, increased risk of complications, timing of surgery, and pain management strategies should occur preoperatively.…”
Section: Considerations For Hip Surgeonsmentioning
confidence: 97%
“…Patients with a history of LSF after THA have been shown to have less improvement in back pain and increased rates of postoperative complications, but no significant alteration in patient-related outcome measures (PROMs), satisfaction, or disability index compared with those without THA 67,68 . These patients also have increased rates of periprosthetic joint infection, revision, and opiate use 45 . This may argue for spinal intervention prior to THA.…”
Section: Considerations For Spine Surgeonsmentioning
confidence: 99%
“…Lumbar Spinal Fusion or THA First Yang et al screened 85,595 patients who underwent THA and identified 1,356 patients who underwent THA before lumbar spinal fusion and 2,016 patients who underwent THA after spinal fusion 31 . The authors found that the patients who underwent THA first had an increased dislocation risk, higher rate of periprosthetic joint infection, surgical site complications, revision, and postoperative opioid use compared with those who underwent THA after lumbar spinal fusion.…”
Section: Current Trends and Debatesmentioning
confidence: 99%